Pengembangan LKPD Berbasis Situation Based Learning Muatan Matematika Materi Bangun Ruang Kelas VI - Shukma Dyah Ayu Kumala; Yuniawatika Yuniawatika; Esti Untari (Universitas Negeri Malang, 2022)
Abstract: Research and development of Situation Based Learning LKPD is conducted to improve the quality of learning and meaningful learning for students in the material of building class VI. LKPD Based on Situation Based Learning is a sheet of activity that contains material and assignments for students with 4 stages including creating mathematical situations, posing mathematical problem, solving mathematical problems, and applying mathematics. In this study using the ADDIE research model with 5 stages, namely Analysis-Design-Develop-Implement Evaluate). Data collection in this study was in the form of a questionnaire (questionnaire) which was given to the validation of material experts, media experts, and class VI teachers as users in the form of quantitative and qualitative data. The results of the validation by material experts showed a percentage of 95 percent, 100 percent of media experts, 93.75 percent of users and 96.9 percent of student response questionnaires, so it can be said that Situation Based Learning LKPD is very valid, practical and usable. Abstrak: Penelitian dan pengembangan LKPD Berbasis Situation Based Learning dilakukan untuk meningkatkan kualitas pembelajaran dan pembelajaran bermakna bagi siswa pada materi bangun ruang kelas VI. LKPD Berbasis Situation Based Learning adalah lembaran aktivitas yang berisi materi dan tugas untuk siswa dengan 4 tahapan meliputi creating mathematical situation, posing mathematical probel, solving mathematical problem, dan applying mathematics. Dalam penelitian ini menggunakan model penelitian ADDIE dengan 5 tahapan yaitu Analysis-Design-Develop-Implement Evaluate). Pengumpulan data dalam penelitian ini berupa angket (kuesioner) yang diberikan kepada validasi ahli materi, ahli media, dan guru kelas VI sebagai pengguna berupa data kuantitatif dan kualitatif. Hasil validasi oleh ahli materi menunjukkan presentase sebesar 95 persen, ahli media sebesar 100 persen, pengguna sebesar 93,75 persen dan angket respon siswa sebesar 96,9 persen, sehingga dapat dikatakan bahwa LKPD Berbasis Situation Based Learning sangat valid, praktis dan dapat digunakan.